2015
DOI: 10.1177/1082013215582275
|View full text |Cite
|
Sign up to set email alerts
|

Development of a convenience and safety chilled sous vide fish dish: Diversification of aquacultural products

Abstract: The dynamic expansion of the ready-to-eat seabream sector in its adaptation to new lifestyles has led to the search for new presentation formats in seabream (Sparus aurata). Green sauce (olive oil, wine vinegar, garlic, fresh parsley, black pepper, basil and salt) and 60 ℃ of cooking temperature were chosen by the panellists for the sous vide cooking process. Seabream fillet and sauce were packaged in polypropylene trays, cooked, chilled and stored at 2 ℃. Microbiological (total viable counts,Enterobacteriacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Alves et al (2020) reported that Salmonella was not detected in pasteurized sous vide tilapia fillets and the coliform bacterial load was reduced by heat treatment. Espinosa et al (2015) reported that the absence of Salmonella and Listeria monocytogenes in sea bream cooked at 60°C sous vide confirmed the food safety of the product. Many researchers (Espinosa et al, 2015; Garcia‐Linares et al, 2004; Gonzalez‐Fandos et al, 2004; Humaid et al, 2020; Nyati, 2000; Ramos et al, 2016; Schellekens, 1996) report that heat treatment is of great importance in ensuring microbial quality and safety in sous vide fish.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Alves et al (2020) reported that Salmonella was not detected in pasteurized sous vide tilapia fillets and the coliform bacterial load was reduced by heat treatment. Espinosa et al (2015) reported that the absence of Salmonella and Listeria monocytogenes in sea bream cooked at 60°C sous vide confirmed the food safety of the product. Many researchers (Espinosa et al, 2015; Garcia‐Linares et al, 2004; Gonzalez‐Fandos et al, 2004; Humaid et al, 2020; Nyati, 2000; Ramos et al, 2016; Schellekens, 1996) report that heat treatment is of great importance in ensuring microbial quality and safety in sous vide fish.…”
Section: Resultsmentioning
confidence: 92%
“…Espinosa et al (2015) reported that the absence of Salmonella and Listeria monocytogenes in sea bream cooked at 60°C sous vide confirmed the food safety of the product. Many researchers (Espinosa et al, 2015; Garcia‐Linares et al, 2004; Gonzalez‐Fandos et al, 2004; Humaid et al, 2020; Nyati, 2000; Ramos et al, 2016; Schellekens, 1996) report that heat treatment is of great importance in ensuring microbial quality and safety in sous vide fish. According to another study, it has been reported that boiled crayfish have a lower bacterial load (Total bacterial count, E coli , Bacillus cereus , Staphylococcus aureus , Salmonella spp, mold, yeast) compared to raw crayfish due to heat treatment (El‐kholie et al, 2012).…”
Section: Resultsmentioning
confidence: 92%
“…In addition, sea cucumber prepared with SV at 70 °C for 60 min had moderate hardness, crispness, smooth taste, and flexibility (Li, 2013). Moreover, Espinosa et al (2016) found that flavor and texture of Sparus aurata were best when cooked at 60 °C for 12-15 min. In addition, it has been suggested that the SV technology can replace pre-treatment of tender meat technology (Suriaatmaja & Lanier, 2014).…”
Section: Impact On Texture Of Aquatic Food Productsmentioning
confidence: 99%
“…In addition, Diaz et al (2009) found that SV applied to salmon (80 °C, 45 min) effectively prevented growth of aerobic and anaerobic psychrophilic bacteria, lactic acid bacteria, molds and yeasts, and Enterobacteriaceae during cold storage. Espinosa et al (2016) discussed the impact of SV on the microbial load of seabream and found that Salmonella and Listeria monocytogenes were not detected in the samples.…”
Section: Impact On Safety Of Aquatic Food Productsmentioning
confidence: 99%